A Hybrid Lister‐Outrigger Probe for Rapid Marine Geothermal Gradient Measurement. Issue 1 (7th January 2021) - Hornbach, Matthew J.; Sylvester, Joshua; Hayward, Chris; Kühn, Michel; Huhn‐Frehers, Katrin; Freudenthal, Tim; Watt, Sebastian F. L.; Berndt, Christian; Kutterolf, Steffen; Kuhlmann, Jannis; Sievers, Carina; Rapp, Sophia; et al.
Abstract: We have successfully constructed and tested a new, portable, Hybrid Lister‐Outrigger (HyLO) probe designed to measure geothermal gradients in submarine environments. The lightweight, low‐cost probe is 1–3 m long and contains 4–12 semiconductor temperature sensors that have a temperature resolution of 0.002°C, a sample rate of <2 s, and a maximum working depth of 2, 100 m below sea level (mbsl). Probe endurance is continuous via ship power to water depths of 700 mbsl or up to 1 week on batteries in depths >500 mbsl. Data are saved on solid‐state disks, transferred directly to the ship during deployment via a data cable, or transmitted via Bluetooth when the probe is at the sea surface. The probe contains an accelerometer to measure tilt, internal pressure, temperature, and humidity gauges. Key advantages of this probe include (1) near‐real‐time temperature measurements and data transfer; (2) a low‐cost, transportable, and lightweight design; (3) easy and rapid two‐point attachment to a gravity corer, (4) short (3–5 min) thermal response times; (5) high temporal/spatial resolution; and (6) longer deployment endurance compared to traditional methods. We successfully tested the probe both in lakes and during sea trials in May 2019 offshore Montserrat during the R/V Meteor Cruise 154/2. Probe‐measured thermal gradients were consistent with seafloor ocean‐drilling temperature measurements. Ongoing probe improvements include the addition of real‐time bottom‐camera feeds and long‐term (6–12 months) deployment for monitoring. Key Points: We have designed, developed, and tested a low‐cost, portable hybrid Lister‐type probe to measure shallow thermal gradients The probe consists of lightweight, quickly interchangeable/expendable components deployable to 2, 100‐m depth The probe provides high vertical and temporal temperature resolution and rapid data transmission, reducing downtime